Pengaruh Kredit Terhadap Perilaku Ekonomi Rumahtangga Petani Padi Sawah:Aplikasi Model Ekonomi Rumahtangga Usahatani - rosmiati, mia (Jurnal Manajemen Teknologi, 2012)
This research aims to analyze the effect of credit on farm household economic behavior and evaluate the impact of access to credit sources and reduction of lending rates on farm household economic behavior. This research used survey method. Data analysis using the simultaneous model (2SLS) and simulation model. Data were collected through a survey of household lowland rice farmers in the district of Sumedang, West Java Province. The results showed that farm household as a unit of production and consumption respond positively to the amount of credit. The amount of credit, led to the increased use of production inputs, output and farm income, which in turn will lead to the increased of consumer spending and demand for hired labor . This indicated that the farm household as a family farming is essentially a household production and household consumption as well, so that production and consumption decisions are not separate, but closely related. Access to sources of credit is more important than a low lending rates.